Keadilan dan Kepastian Hukum dalam Pemenuhan Hak Anak Pasca Perceraian - Huda, M. Al Amin Ilman; Tohari, Ilham (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2025)
This article explores the challenges and solutions related to the fulfillment of child support after divorce, from the perspective of justice and legal certainty. Although various regulations—such as the Marriage Law, Child Protection Law, and the Compilation of Islamic Law—clearly define parental responsibilities, their implementation often fails in practice. Key contributing factors include limited legal awareness, high execution costs, the absence of the non-custodial parent, and weak enforcement of court rulings. The study highlights the need to strengthen both substantive justice and judicial mechanisms to ensure the protection of children's rights. The article also advocates for adaptive and participatory approaches, such as adjusting the amount of support in line with economic changes and involving children in legal decisions. The government is urged to enhance institutional coordination and expand access to legal aid. By integrating the principles of justice and legal certainty, Indonesia’s legal system can better protect children affected by divorce and encourage parents to fulfill their responsibilities in both legal and social contexts.